2023
DOI: 10.1111/vsu.13955
|View full text |Cite
|
Sign up to set email alerts
|

Comparative kinetic and kinematic evaluation of TPLO and TPLO combined with extra‐articular lateral augmentation: A biomechanical study

Abstract: Objectives To investigate stifle kinematics and kinetics following TPLO and TPLO combined with an extra‐articular lateral augmentation (TPLO‐IB) during the tibial compression test (TCT) and the tibial pivot compression test (TPT), applied with an external (eTPT) and an internal moment (iTPT). Study design Experimental ex vivo study. Sample population Ten cadaveric hindlimbs of dogs weighing 23–40 kg. Methods 3D‐kinematic and kinetic data were collected while performing TCT, eTPT, and iTPT and compared under th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The study suggested that adding an extra-articular lateral augmentation might be more successful in re-establishing stifle kinematics than TPLO alone. 29 In the present case, a lateral augmentation suture was applied successfully to neutralise residual cranial tibial translation and internal tibial rotational instability.…”
Section: Discussionmentioning
confidence: 76%
“…The study suggested that adding an extra-articular lateral augmentation might be more successful in re-establishing stifle kinematics than TPLO alone. 29 In the present case, a lateral augmentation suture was applied successfully to neutralise residual cranial tibial translation and internal tibial rotational instability.…”
Section: Discussionmentioning
confidence: 76%